Binegative Myths in Pornography: An Examination of Sexual Behaviors and Aggression by Sexual Identity Categories. Issue 2 (18th August 2021) - Bowling, Jessamyn; Fritz, Niki
Abstract: Research suggests individuals may learn sexual attitudes and behaviors from consuming pornography. Sexual minoritized individuals (e.g. gay, lesbian, bisexual) are more likely to use online sources to learn about their identity. Therefore, the content of free online pornographic videos is important to examine. Yet there is limited research on the depiction of sexual minoritized women in pornography. This study compared the frequencies of sexual behaviors and aggression in Heterosexual ( n = 594), Lesbian ( n = 108), and Bisexual ( n = 105) pornographic scenes. Compared to Heterosexual scenes, Bisexual scenes contained higher frequencies of sexual behaviors including fellatio, penile-vaginal sex, and anal sex. Lesbian scenes had the most depictions of female orgasm when compared to Bisexual and Heterosexual scenes, while Bisexual scenes had more depictions of male orgasm when compared to Heterosexual. There was no statistical difference in aggression toward women among categories; Bisexual scenes, however, had more depictions of aggression against men than Heterosexual scenes. These findings suggest binegative myths like hypersexuality are present in pornography.